2012
DOI: 10.5402/2012/658095
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Tests in Sickle-Cell Patients in Benin City

Abstract: Background. Sickle-cell disease (SCD) is a life-long haematological disorder characterized by red blood cells that assume an abnormal, rigid, sickle shape and with high prevalence in West Africa. Sickle cell disease (SCD) is one of the most common genetic disorders among Africans as indicated in Akinyanju (1989). 61.4% of the children born annually with haemoglobinopathies worldwide have been reported to have SCD and they are from Africa as shown in World Health Organization Report (1987). Hypoxaemia is the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…Most of the original studies are from western Nigeria. 13 , 14 This study could therefore corroborate or refute regional or ethnic differences in lung function in children with SCD. The study hypothesis seeks to answer the following questions?…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Most of the original studies are from western Nigeria. 13 , 14 This study could therefore corroborate or refute regional or ethnic differences in lung function in children with SCD. The study hypothesis seeks to answer the following questions?…”
mentioning
confidence: 62%
“… 18 , 19 have alsoreported marginally, but not significantly higher values of lung function tests in healthy males compared with healthy females with HbAA genotype. 6 In the contrary, Oko-Ose et al 14 found significantly higher mean values of respiratory function tests in females compared with the males. The higher values of weight and body surface areas in females explained the gender variations.…”
Section: Discussionmentioning
confidence: 91%
“…The observed impaired ventilatory functions were explained by the reduction of lung compliance which may be due to repeated episodes of ACS or sickle‐cell‐related vasculopathy . Similar to our results, Oko‐Ose et al showed that the most common PFTs abnormality in adults with SCD was restrictive disease pattern (76.7%) and that OLD was relatively uncommon (23.3%). Moreover, Alameri et al found that nearly half (51%) of adults Saudi with SCD had abnormal PFTs; 36% of them had a restrictive pattern.…”
Section: Discussionmentioning
confidence: 99%
“…All patients performed spirometry using JAEGER apparatus (Hoechberg, Germany) to measure the following parameters: forced vital capacity (FVC), forced expiratory volume in first second (FEV 1 ), ratio between FEV1 and FVC (FEV 1 /FVC%) and forced expiratory flow rate during 25‐75% of expiration (FEF25‐75%). Standard methodology for acceptability of spirometry was followed as described by previous studies . Patients were excluded if the effort was not technically acceptable; if they were younger than 10 years of age and exhaled for less than 3 s or if they were older than 10 years of age and exhaled for less than 6 s.…”
Section: Radiological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation